Religious catechism in serbian schools since 1990 until today (reasons for implementation, actual situation and perspectives) - Todorović, Dragan; Đorđević, Dragoljub; Kuburić, Zorica (Sociološki pregled, 2024)
Religious education was introduced into the system of institutional education in Serbia in the autumn of 2001. The decision on the new subject was made at the political level, in line with a special decree by the Serbian government and Zoran Đinđić, PhD, Serbian Prime Minister at the time, without an official approval of the relevant ministry. After two decades of teaching Religious Education in the Serbian educational system, a question arises about the assessment of the results and impact of religious education in Serbian state-funded primary and secondary schools. To what extent do the secular school program, based on positive scientific knowledge, and the dogmatic confessional approach to matters of socialization and upbringing of complete persons coincide or clash with each other? Following a short historical overview of the presence of religious education in Serbia, the focus of this paper is to offer a critical review of religious education textbooks and the status of religious education teachers, achievements and effects of two-decade implementation of religious catechism in Serbian schools, functions of religious education in state-funded schools, and present-day discussions of Serbian experts of different profiles regarding the place and advantages of the confessional model of religious catechism in Serbia’s educational system. At the end of the paper, the authors submit a proposal for the ways in which religious education can be improved in Serbia.